High temperature suppression of dioxins. (March 2016) - Zhan, Ming-Xiu; Chen, Tong; Fu, Jian-Ying; Lin, Xiao-Qing; Lu, Sheng-Yong; Li, Xiao-Dong; Yan, Jian-Hua; Buekens, Alfons
Abstract: Combined Sulphur-Nitrogen inhibitors, such as sewage sludge decomposition gases (SDG), thiourea and amidosulphonic acid have been observed to suppress the de novo synthesis of dioxins effectively. In this study, the inhibition of PCDD/Fs formation from model fly ash was investigated at unusually high temperatures (650 °C and 850 °C), well above the usual range of de novo tests (250–400 °C). At 650 °C it was found that SDG evolving from dried sewage sludge could suppress the formation of 2, 3, 7, 8-substituted PCDD/Fs with high efficiency (90%), both in weight units and in I-TEQ units. Additionally, at 850 °C, three kinds of sulphur-amine or sulphur-ammonium compounds were tested to inhibit dioxins formation during laboratory-scale tests, simulating municipal solid waste incineration. The suppression efficiencies of PCDD/Fs formed through homogeneous gas phase reactions were all above 85% when 3 wt. % of thiourea (98.7%), aminosulphonic acid (96.0%) or ammonium thiosulphate (87.3%) was added. Differences in the ratio of PCDFs/PCDDs, in weight average chlorination level and in the congener distribution of the 17 toxic PCDD/Fs indicated that the three inhibitors tested followed distinct suppression pathways, possibly in relation to their different functional groups of nitrogen. Furthermore, thiourea reduced the (weight) average chlorinated level. In addition, the thermal decomposition of TUA was studied by means of thermogravimetry-fourier transform infrared spectroscopy (TG-FTIR) and the presence of SO2, SO3, NH3 and nitriles (N≡C bonds) was shown in the decomposition gases; these gaseous inhibitors might be the primary dioxins suppressants. Highlights: S–N inhibitors could suppress dioxins at high temperature effectively. Thermal decomposition of TUA was studied by TG-FTIR. The form of N and the (S + N)/Cl molar ratio could affect dioxins suppression effect.